Role of Aqueous Plant Extracts, Humic Acid, and Salicylic Acid in Inhibition of Rhizoctonia Solani and Fusarium Incarnatum in Vitro - Hussein Ali Salim; Noora Bandar Maizar; Mohammed Saheb Abed; Ali Faisal Aziz Al-Qaisi; Idrees Ghalib Idrees Al-tamimi; Marym Jamal Mohmmed Ali; Noor Tariq Abid; Falah Hassan Khalil (American Journal of Biodiversity, 2026)
A laboratory experiment was carried out at a plant protection laboratory, Directorate of Diyala Agriculture, Iraq, during the season 2024 to evaluate the impact of aqueous plant extracts, viz., Salvia officinalis, Silybum marianum, and Urtica dioica, as well as salicylic acid and humic acid on the inhibition percentage of Rhizoctonia solani and Fusarium incarnatum in vitro. The findings revealed that the aqueous plant extracts such as S. offisinalis at concentrations of 30%, U. dioica at 20%, and S. marianum at 30% led to an increase in the inhibition percentage of F. incarnatum, which reached 59.25%, 69.99%, and 35.18%, respectively, while extracts of S. offisinalis at concentrations of 30%, U. dioica at 20%, and S. marianum at 10% resulted in an increase in the inhibition percentage of R. solani, which amounted to 6.47%, 54.62%, and 34.25%, respectively. whereas humic acid at a concentration of 5% was superior in the inhibition percentage of F. incarnatum (48.14%) and R. solani (100.00%), and salicylic acid at a concentration of 0.5 ppm was outstanding in the inhibition percentage for each of F. incarnatum and R. solani (100.00 ppm).